2007
DOI: 10.1007/s00134-007-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Variability in outcome and resource use in intensive care units

Abstract: Objective: To examine variability in outcome and resource use between ICUs. Secondary aims: to assess whether outcome and resource use are related to ICU structure and process, to explore factors associated with efficient resource use. Design and setting: Cohort study, based on the SAPS 3 database in 275 ICUs worldwide. Patients: 16,560 adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 44 publications
2
99
1
4
Order By: Relevance
“…The lower satisfaction observed in ICUs with written admission/discharge policies was an unexpected finding and is difficult to explain. Indeed, some organizational parameters have been found to improve resource use and outcome [4]. In the present study, however, apart from the patient:nurse ratio, no other organizational parameter was associated with increased satisfaction.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The lower satisfaction observed in ICUs with written admission/discharge policies was an unexpected finding and is difficult to explain. Indeed, some organizational parameters have been found to improve resource use and outcome [4]. In the present study, however, apart from the patient:nurse ratio, no other organizational parameter was associated with increased satisfaction.…”
Section: Discussioncontrasting
confidence: 67%
“…Over time, interest has focused on additional aspects, such as quality of life [1,2], processes of care [3] and resource use [4]. Recently, outcome research has been extended to the care of patients and their next of kin [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous comparisons of case-mixadjusted ICU length of stay across units also have demonstrated significant differences in OMELOS across units (7)(8)(9)(10)(11)(12)(13)(14). Some of these studies assessed the association between ICU OMELOS with standardized mortality ratios across multiple units and found that little association existed (7)(8)(9).…”
Section: Discussionmentioning
confidence: 89%
“…-Presence of inter-professional clinical rounds [46] -Standardized and structured processes of handover and of interdisciplinary and interprofessional information transfer -Use of a clinical information system (patient data management system) Finally, although beyond the scope of these recommendations, it needs to be mentioned that a growing body of literature indicates that management and climate in the ICU can influence the satisfaction of patient relatives, the well-being of health care workers, and might even have an impact on patient outcomes [9-11, 47, 48].…”
Section: Activity Criteriamentioning
confidence: 99%